2012
DOI: 10.3109/17518423.2012.662660
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of insistence on sameness in an 11-year old boy with Asperger syndrome

Abstract: Problem behaviours related to insistence on sameness may be motivated by different consequences depending on the scenario created.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Clear functions of problem behavior associated with ritual interruption were obtained for all participants using the access‐to‐rituals condition of the functional analysis. These results support previous findings (Hagopian et al, ; Hausman et al, ; Kuhn et al, ; Murphy et al, ; Ollington et al, ; Sigafoos et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Clear functions of problem behavior associated with ritual interruption were obtained for all participants using the access‐to‐rituals condition of the functional analysis. These results support previous findings (Hagopian et al, ; Hausman et al, ; Kuhn et al, ; Murphy et al, ; Ollington et al, ; Sigafoos et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Several previous studies have conducted functional analyses of problem behaviors occasioned by the interruption of rituals or stereotypy (Hagopian, Bruzek, Bowman, & Jennett, ; Hausman, Kahng, Farrell, & Mongeon, ; Kuhn, Hardesty, & Sweeney, ; Lang et al, ; Murphy, Macdonald, Hall, & Oliver, ; Ollington, Green, O'Reilly, Lancioni, & Didden, ; Rodriguez, Thompson, Schlichenmeyer, & Stocco, ; Sigafoos et al, ). Hausman et al () assessed ritualistic door opening and closing using functional analysis.…”
mentioning
confidence: 99%
“…Research has shown that repetitive and stereotyped behaviors were found to be a good predictor of anxiety symptoms in the ASD and ID population (Rodgers & Ofield, 2018 ; Sáez Suanes, 2021 ). Several authors propose the increase of a particular type of repetitive behavior, insistence on invariance, as a protective or reductive tool for anxiety symptoms (Ollington et al, 2012 ; Rodgers et al, 2012 ). Future lines of research should consider the relationship between these variables especially in women with ASD as they are more prone to develop anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Although subjective, parents can report information about several situations and about behaviors which might not be observed in a short assessment. However, in vivo assessment of behavioral flexibility in naturalistic settings and multiple informants (e.g., teachers) completing the BFRS-R would have strengthened the study (see for example: Green et al, 2008;Ollington et al, 2012). An additional limitation was the uneven sample sizes, including the small sample size for the group of children with PDD-NOS plus ID compared to those with autistic disorder plus ID, which may have influenced the findings.…”
Section: Discussionmentioning
confidence: 99%